Perilaku informasi penggemar grup k-pop NCT Dream di media sosial Twitter - Fikrisya Ariyani Iskandar; Laksmi Laksmi; Indira Irawati; Luki Wijayanti (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This paper investigate information behavior of NCT Dream fans (The South Korean Boy Band) on Twitter. Previously, from research perspectives, fan behavior and their information behavior studies have not been discussed deeply. Fans have unique ways to use information by collaboratively creating, organizing, disseminating, and sharing information. Research Methods. The paper used a virtual ethnographic research method with a qualitative approach. Observations were conducted to explore the exchange of information and interaction between fans with text, images, video and audio among fellow fans. Data was collected by observations, researchers played a role as participants. Data Analysis. The paper followed the three stages of coding: open coding, axial coding, selective coding. Results and Discussion. Fans are able to create their own information, which later it is considered as community knowledge, although the source of information is not official. The fans demonstrate collaborative, creative, sharing, and performative activities that engage further with information. Conclusion. Fan information behavior involves information creation, information organization, information production, and production. Information behavior of fans on Twitter is informal, diverse, and evolving from the model of fan information behavior offered by Price. Furthermore, because fan behavior has shifted to textual productivity, this information behavior model is very helpful in identifying fans on social media. However, crowdfunding appear as one additional behavior inPrice's information behavior model.